Animal Models of Urologic Chronic Pelvic Pain Syndromes: Findings From the Multidisciplinary Approach to the Study of Chronic Pelvic Pain Research Network - Lai, Henry; Gereau, Robert W.; Luo, Yi; O'Donnell, Michael; Rudick, Charles N.; Pontari, Michel; Mullins, Chris; Klumpp, David J. (Urology (Ridgewood, N.J.), 2015)
To describe the approach taken by the Multidisciplinary Approach to the Study of Chronic Pelvic Pain Research Network investigators to advance the utility of urologic chronic pelvic pain syndromes (UCPPS) animal models. A multidisciplinary team of investigators representing basic science and clinical expertise defined key phenotypic criteria for rodent models of UCPPS. UCPPS symptoms were prioritized based on their clinical significance. Methods for quantifying animal correlates to patient symptoms were developed. The methods were implemented across proposed rodent models for evaluation and comparison of animals for phenotypic characteristics relevant to human symptomatology. Pelvic pain and urinary frequency were deemed primary features of human UCPPS and were prioritized for assessment in animals. Nociception was quantified using visceromotor response to bladder distention and by applying von Frey filaments to the lower abdomen (referred tactile allodynia). Micturition activity was assessed as free voiding using micturition cages or blotting pad assays and in response to bladder filling by cystometry. Models varied in both depth of characterization and degree of recapitulating pelvic pain and urinary frequency characteristics of UCPPS. Rodent models that reflect multiple key characteristics of human UCPPS may be identified and provide enhanced clinical significance to mechanistic studies. We have developed a strategy for evaluating current and future animal models of UCPPS based on human symptomatology. This approach provides a foundation for improved translation between mechanistic studies in animals and clinical research and serves as a validation strategy for assessing validity of models for symptom-driven disorders of unknown etiology.